Selection of Graphite Pencil Grades for the Design of Suitable Electrodes for Stacking Multiple Single‐Inlet Paper‐Pencil Fuel Cells. Issue 1 (3rd January 2019) - Arun, Ravi Kumar; Gupta, Vinay; Singh, Preeti; Biswas, Gautam; Chanda, Nripen
Abstract: We present a single‐inlet paper‐pencil based microfluidic fuel cell which works on the capillary driven fluid flow of a mixture of fuel (formic acid) and electrolyte (dilute sulfuric acid) solutions as a single entity. Different types of pencils are used to prepare the graphite electrodes to observe their effect on the fuel cell performance. The graphite electrodes are porous and act as a gas diffusion electrode which breaths in oxygen directly from the quiescent air and out CO2 from the cell. The paper fuel cell also fabricated in different dimensions and connected as cell‐stacks to enhance its performance. The paper‐pencil device generates maximum open circuit potential of ∼2.5 V in series combination and maximum current density of ∼ 82 mA cm −2 and power density of ∼ 100 mW cm −2 in parallel combination. Later, rGO−Cu/CuO nanocomposite embedded electrodes are used to observe their effect on the device performance. Abstract : A single‐inlet paper‐based microfluidic fuel cell demonstrated which works on capillary action of a fluid that consists of a mixture of fuel (formic acid) and electrolyte (diluted sulfuric acid) solutions. Different grades of pencils are used to fabricate the graphite electrodes to study the performance of the fuel cell. Finally, the miniaturized fuel cells stacked to draw more energy for potential applications.